The Application Of Shariah Hotels Concept At Bandung City - Muhammad Syakib Asqalani Rifai (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Several countries in the world have developed sharia tourism in capturing economic potential in it, including Japan, South Korea, Malaysia, Turkey, Saudi Arabia, United Arab Emirates and Qatar. Indonesia as a country that has the world's largest Muslim population continues to strive to develop the sharia tourism industry.Sharia hotels are hotels using sharia principles in terms of services, facilities and even services that are in accordance with the provisions in providing guest benefit services. In the implementation of Islamic hotels, there are various polemics that come from various parties. In general, management at those hotels of research place has approached Sharia principles, but there are still some points that need to be developed to be more ideal as a syariah hotel